2015
DOI: 10.21273/horttech.25.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Early Spring Bulbs into Dormant Warm-season Turfgrasses

Abstract: Many early spring bulb species are naturally found in grassy areas such as meadows or lawns. However, few studies have been conducted to define this concept in maintained lawns, especially warm-season lawns such as zoysiagrass (Zoysia japonica) or bermudagrass (Cynodon dactylon). Four early spring bulb species, including two crocus species (Crocus tommasinianus ‘Ruby Giant’ and Crocus chrysanthus Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that establishing early-spring flowering bulbs into areas of zoysiagrass and bermudagrass is an appropriate practice for those who desire color and biodiversity in a dormant lawn (Mirabile et al, 2016;Richardson et al, 2015). The daffodil 'Rip Van Winkle' was tested in both the present trial and the study by Mirabile et al (2016), and it showed persistence over time in transition zones of the United States and Italy.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Previous studies have shown that establishing early-spring flowering bulbs into areas of zoysiagrass and bermudagrass is an appropriate practice for those who desire color and biodiversity in a dormant lawn (Mirabile et al, 2016;Richardson et al, 2015). The daffodil 'Rip Van Winkle' was tested in both the present trial and the study by Mirabile et al (2016), and it showed persistence over time in transition zones of the United States and Italy.…”
Section: Resultsmentioning
confidence: 69%
“…Crocus tommasinianus Herb. 'Ruby Giant' demonstrated persistence in zoysiagrass at this location in a previous trial and was included as a positive control (Richardson et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and buffalograss [Bouteloua dactyloides (Nutt.) Columbus] have successfully demonstrated ability to support flowering bulbs (Richardson et al, 2015;Wisdom et al, 2019), but other warm-season turfgrass species such as Eremochloa Buese and Stenotaphrum Trin. species might also be evaluated for ability to host forbs for pollinator forage.…”
Section: Speciesmentioning
confidence: 99%
“…Some studies have explored the possibility of double-cropping forbs and bulbous species in warm-season lawns with the intent to maintain, rather than replace, the lawn [5][6][7][8]. These studies focused on flower production, the ability to withstand mowing, and the potential to provide an early season habitat and nectar source for beneficial insects.…”
Section: Introductionmentioning
confidence: 99%